Identification of bird species in West Sumatra, as main component for developing local wealth-based teaching materials at university - Relsas Yogica; Yosi Laila Rahmi; Helsa Rahmatika; Mutiara Ratu Salsabila; Arif Rahmat Ramadhan (Universitas Negeri Padang, 2023)
Google's developments, such as Google Lens, are increasingly providing opportunities and challenges to the world of education. These challenges and opportunities can be used as a way for lecturers as educational actors to explain the situation and solve student problems quickly, accurately, and precisely. So that lecturers need an innovative effort by utilizing Google Lens in lectures, especially in the field of biology. Google Lens is used as an identifier of an object, such as a bird, more effectively and efficiently. This study aims to produce initial data for the development of biology teaching materials at universities that are locally based and to find out the effectiveness of Google Lens as a bird species identifier in Padang City, West Sumatera, as well as to improve students' digital literacy skills, especially in Biology Department, Mathematics and Natural Science Faculty, Universitas Negeri Padang. This research went through stages including 1) collecting bird photos, 2) selecting photos to upload to Google Lens, 3) uploading photos to Google Lens, and 4) data confirmation. Bird photos were taken in various places in Padang city, West Sumatera, as well as at several locations in the adjoining cities, in the morning and evening. Confirm data using the https://ebird.org/ site and John MacKinnon's field book. As many as 60 bird species are documented and recognized on Google Lens. This study concluded that Google Lens is effectively used to recognize bird photos, by matching them to relevant internet sites. There are limitations to the quality of the photo and the angle of view of the photo, which results in a long time for object recognition.